2018
DOI: 10.1007/s00380-018-1133-5
|View full text |Cite
|
Sign up to set email alerts
|

The first multicenter, randomized, controlled trial of home telemonitoring for Japanese patients with heart failure: home telemonitoring study for patients with heart failure (HOMES-HF)

Abstract: Home telemonitoring is becoming more important to home medical care for patients with heart failure. Since there are no data on home telemonitoring for Japanese patients with heart failure, we investigated its effect on cardiovascular outcomes. The HOMES-HF study was the first multicenter, open-label, randomized, controlled trial (RCT) to elucidate the effectiveness of home telemonitoring of physiological data, such as body weight, blood pressure, and pulse rate, for Japanese patients with heart failure (UMIN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 33 publications
1
67
0
3
Order By: Relevance
“…12) In the "HOMES-HF" study carried out in Japan, Kotooka stated that one possible reason for non-improvement in the rehospitalization rate was due to the lack of interactive communication. 13) In our study, we provided collaborative support through a nurse and health care workers, rather than only focusing on vital signs. Thus, the effectiveness of telemonitoring seems to be a result of direct interaction with healthcare workers who can arrange and provide comprehensive care for pa-tients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12) In the "HOMES-HF" study carried out in Japan, Kotooka stated that one possible reason for non-improvement in the rehospitalization rate was due to the lack of interactive communication. 13) In our study, we provided collaborative support through a nurse and health care workers, rather than only focusing on vital signs. Thus, the effectiveness of telemonitoring seems to be a result of direct interaction with healthcare workers who can arrange and provide comprehensive care for pa-tients.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for not finding significant benefits of telemonitoring on rehospitalization is the absence of interactive communication between patients and their healthcare providers. 12,13) As most patients with HF are elderly people suffering from comorbid conditions with severe symptoms, they need medical advice and support in their daily household affairs. Hence, we advocated that timely feedback for assessment, appropriate care coordination, and enhancement of patient self-management should be embedded within the alarming system of a telemonitoring program which we considered as collaborative management (CM).…”
mentioning
confidence: 99%
“…Results from studies are not consistent regarding outcomes of TM. Some studies have shown that TM may improve survival, reduce HF-related hospitalizations, and improve quality of life compared with usual care or low access to care [2,13,14]; other studies have shown no improvements [15-17]. Furthermore, noninvasive TM studies have methodological weaknesses such as insufficiencies regarding large sample size, homogenous protocols, robust designs, a clear definition of noninvasive TM, and show a diversity of outcomes [5,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 This is thought to be due largely to low adherence to monitoring. A similar telemonitoring study was also performed in Japan; 25 in that study, adherence to monitoring was favorable, owing to the interventions of home healthcare nurses. Unfortunately, there was no significant difference in the readmission rate compared with the usual care group.…”
Section: Applying Ict To Home-based Care For Patients With Hfmentioning
confidence: 91%